A reputation‐based RPL protocol to detect selective forwarding attack in Internet of Things. (11th October 2021) - Patel, Anshuman; Jinwala, Devesh
Summary: Internet of Things (IoT) is an internet of smart objects where smart objects communicate with each other. IoT objects are deployed in open medium with dynamic topology. Due lack of infrastructure and centralized management, IoT present serious vulnerabilities to security attacks. Therefore, security is an essential prerequisite for the real‐world deployment of IoT. In this work, we propose reputation‐based RPL protocol where reputation‐based mechanism is embedded into RPL protocol to enhance its capabilities against selective forwarding attack. Reputation is calculated by evaluating data forwarding behavior of IoT node. Data forwarding behavior of IoT node is evaluated by the difference between monitored actual packet loss and estimated normal loss. Calculated reputation value is considered in parent selection. Simulation results show that the proposed approach can accurately detect and isolate selective forwarding attack with improving data delivery ratio of the IoT network. Abstract : The selective forwarding attack is detected based on the packet forwarding behavior of Internet of Things (IoT) node which is evaluated by the difference between monitored actual packet loss and estimated normal packet loss.